Agroecological Transitions: From Theory to Practice in Local Participatory Design - Bergez, Jacques-Eric.; Audouin, Elise; Therond, Olivier; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
There is wide agreement on the need to change the prevalent agricultural models, given their negative impacts and their incompatibility with current societal issues. Agroecological transition has been promoted as a potential solution to the ecological, social and economic problems generated by these models. It however involves a systemic, multi-scale and transdisciplinary process. Due to this complexity, the overall picture of what farms and food systems "actually are" and "might be" may not be apparent at the individual level. Yet individuals' knowledge and values provide complementary insights on how to proceed in deepening ecological modernisation. Expertise can also provide landmarks to be considered in that process. Because local stakeholders' experience and skills are key resources in the adaptation and adoption of agroecological transition, new conceptual and methodological frameworks and tools have to be developed to support them in the design process of such a complex transition. This book presents feedback from the 'Territorial Agroecological Transition in Action'- TATA-BOX research project, which was devoted to these specific issues. The multidisciplinary and multi-organisation research team steered a four-year action-research process in two territories of France. This book presents: i) the key dimensions to be considered when dealing with agroecological transition: diversity of agriculture models, management of uncertainties, polycentric governance, autonomies, and role of actors' networks; ii) an operational and original participatory process and associated boundary tools to support local stakeholders in shifting from a shared diagnosis to a shared action plan for transition, and in so doing developing mutual understanding and involvement; iii) an analysis of the main effects of the methodology on research organisation and on stakeholders' development and application; iv) critical analysis and foresights on the main outcomes of TATA-BOX, provided by external researchers.".
Foreword -- Chapter 1: General introduction -- Chapter 2: TATA-BOX at a glance -- Part I: Territorial Agroecological Transition at a concept crossroads -- Chapter 3: Socio-economic characterisation of agriculture models -- Chapter 4: An integrated approach to livestock farming systems' autonomy in designing and managing agroecological transition at the farm and territorial levels -- Chapter 5: Agroecological transition from farms to territorialised agri-food systems: issues and drivers -- Chapter 6: A plurality of viewpoints regarding the uncertainties of the agroecological transition -- Chapter 7: Towards an integrated framework for the governance of a territorialised agroecological transition -- Chapter 8: The key role of actors in the agroecological transition of farmers: a case-study in the Tarn-Aveyron Basin -- Part II: Support methodology for territorial agroecological transition design, and feedback from the TATA-BOX project experience -- Chapter 9: Participatory methodology for designing an agroecological transition at local level -- Chapter 10: Towards a reflective approach to research project management -- Chapter 11: Evaluation of the operationalisation of the TATA-BOX process -- Part III: New prospects and cross-cutting perspectives -- Chapter 12: Information and communication technology (ICT) and the agroecological transition -- Chapter 13: TATA-BOX: A model for participatory processes? -- Chapter 14: Review and Critique of the TATA-BOX Model -- Chapter 15: Opening the TATA-BOX to raise new questions on agroecological transition.
Keywords: Agriculture; Sustainable development; Soil science; Soil conservation; Environmental education; Environmental law; Environmental policy; Agriculture; Sustainable Development; Soil Science & Conservation; Environmental and Sustainability Education; Environmental Law/Policy/Ecojustice.